Action Mechanisms of Metformin Combined with Exenatide and Metformin Only in the Treatment of PCOS in Obese Patients - Jingwen Gan; Jie Chen; Rui-lin Ma; Yan Deng; Xue-song Ding; Shi-yang Zhu; Ai-jun Sun (International Journal of Endocrinology)
Background. Polycystic ovary syndrome (PCOS) is the most common endocrine disease in women of reproductive age, whose clinical characteristics are hyperandrogenism (HA), ovulatory dysfunction, and polycystic ovary, often accompanied by insulin resistance (IR) and metabolic abnormalities. Glucagon-like peptide (GLP)-1 receptor agonists (GLP-1Ra), such as exenatide, can bind to specific receptors on tissues such as the ovaries to improve the clinical phenotype of PCOS, while insulin-sensitizing agents, such as metformin, can also benefit to metabolic abnormalities in PCOS. Liquid chromatography-mass spectrometry (LC/MS) metabolomics revealed differences between the mechanisms of exenatide and metformin treatment of PCOS to some extent. Methods. In this study, 50 obese subjects with PCOS were randomly divided into the exenatide combined with metformin group (COM group, n = 28) and the metformin group (MF group, n = 22) for 12-week treatment. Before and after, serum samples were subjected to LC/MS analysis. Results. After treatment, there were 153 named differential metabolites in the COM group and 99 in the MF group. Most phosphatidylcholines (PC) and deoxycholic acid 3-glucuronide (DA3G) were significantly upregulated, while most glycerophosphoethanolamine (PE-NMe2), glycerophosphocholine (GPC), and threonine were downregulated in both groups. Only the decrease of neuromedin B, glutamate, and glutamyl groups and the increase of chenodeoxycholic acid sulfate docosadienoate (22: 2n6), and prostaglandin E2 have been observed in the COM group. In addition, salicylic acid and spisulosine increased and decanoylcarnitine decreased in the MF group. Both groups were enriched in glycerophospholipid, choline, and sphingolipid metabolism, while the COM group was especially superior in the glutamine and glutamate, bile secretion, and amino acid metabolism. Conclusion. Compared with metformin alone in the treatment of PCOS, the differential metabolites of the exenatide combined with metformin group are more extensive. The COM group may act on the hypothalamic-pituitary-gonadal axis (HPO) and its bypass, regulate multiple metabolism pathways such as phospholipids, amino acids, fatty acids, carnitine, bile acids, and glucose directly or indirectly in obese PCOS patients.